Learning from SARS : preparing for the next disease outbreak : workshop summary - Knobler, Stacey (National Academies Press, 2004)
The report examines the response to SARS by public health systems within individual countries; the biology of the SARS coronavirus and related coronaviruses in animals; the economic and political fallout of the SARS epidemic; quarantine law and other public health measures that apply to combating infectious diseases; and the role of international organizations and scientific cooperation in halting the spread of SARS. The report provides an illuminating survey of findings from the epidemic, along with an assessment of what might be needed in order to contain any future outbreaks of SARS or other emerging infections.